Association of Serum Vitamin D Levels and Stress Fractures in Collegiate Athletes. Issue 12 (9th December 2020) - Millward, David; Root, Allison D.; Dubois, Jeremy; Cohen, Randall P.; Valdivia, Luis; Helming, Bruce; Kokoskie, Justin; Waterbrook, Anna L.; Paul, Stephen
Background: Low vitamin D levels along with high-intensity athletic training may put an athlete at increased risk for a stress fracture. Purpose: To assess whether supplementation with vitamin D is associated with a reduced risk of stress fractures in college athletes. We also assessed differences in vitamin D levels among athletes participating in outdoor versus indoor sports. Study Design: Cohort study; Level of evidence, 2. Methods: The study participants included 802 National Collegiate Athletic Association Division I intercollegiate athletes (497 men and 305 women) on a sports team for at least 1 semester from 2012 to 2018. All athletes who had a baseline vitamin D level in their medical record were included. Athletes with vitamin D levels <40 ng/mL were given vitamin D supplements. We assessed differences in the rate of stress fracture among those who maintained or improved vitamin D levels to ≥40 ng/mL and those who did not, as well as differences in average baseline vitamin D levels by sport type (indoor vs outdoor). Results: The rate of stress fracture was 12% higher (95% CI, 6-19; P < .001) for those who remained low in vitamin D compared with those who were low at baseline but improved their vitamin D status to ≥40 ng/mL. The rate of stress fracture was also 12% higher (95% CI, 5-18; P < .001) for those who had low vitamin D levels compared with those who maintained normal levels. The mean baseline vitamin D values were significantly higher for men participating in outdoor sports versus indoor sports. For men, the mean vitamin D level was 5.7 ng/mL higher (95% CI, 0.9-10.5; P = .01) in outdoor athletes. For women, the mean vitamin D level was 3.7 ng/mL higher (95% CI, –0.58 to 8.03; P < .04) for outdoor versus indoor sports. Conclusion: Study results indicated that correcting low serum vitamin D levels reduces the risk of stress fracture. This study also presented evidence that athletes who participate in indoor sports may be at greater risk for vitamin D deficiency than those who compete in outdoor sports.